Validasi Proses Sterilisasi Menggunakan Otoklaf Dan Uji Stabilitas Real Time Infus Nacl 0,9 % 500 Ml Lembaga Biomedis - Sugindro Sugindro (JURNAL KESEHATAN DELIMA PELAMONIA, 2022)
Labiomed infusion needs to be tested for stability and it is necessary to determine the expiration time of Labiomed infusion based on the market product expiration date. The aim of the study was to validate the Labiomed sterilization process and real time stability test of Labiomed 0.9% NaCl infusion to ensure product stability. The research method is an experimental study using the real time stability method The real time stability test methodology of 0.9% NaCl infusion follows reaction order 0, Shelf-Life Five years. The results showed that the infusion rate of NaCl 0.9% was stable and qualified, namely the content was still between 95% to 105%. The 0.9% NaCl infusion solution meets the requirements of the Indonesian Pharmacopoeia, namely the levels meet the requirements between 95% to 105% with a five-year shelf-live. Keywords: validation, real time stability test, shelf-life, reaction order, NaCl 0,9 % infusion